Differential hypothalamic leptin sensitivity in obese rat offspring exposed to maternal and postnatal intake of chocolate and soft drink - Kjaergaard, M (Nutr Diabetes, 2017)
BACKGROUND/OBJECTIVE: Intake of high-energy foods and maternal nutrient overload increases the risk of metabolic diseases in the progeny such as obesity and diabetes. We hypothesized that maternal and postnatal intake of chocolate and soft drink will affect leptin sensitivity and hypothalamic astrocyte morphology in adult rat offspring. METHODS: Pregnant Sprague-Dawley rats were fed ad libitum chow diet only (C) or with chocolate and high sucrose soft drink supplement (S). At birth, litter size was adjusted into 10 male offspring per mother. After weaning, offspring from both dietary groups were assigned to either S or C diet, giving four groups until the end of the experiment at 26 weeks of age. RESULTS: As expected, adult offspring fed the S diet post weaning became obese (body weight: P<0.01, %body fat per kg: P<0.001) and this was due to the reduced energy expenditure (P<0.05) and hypothalamic astrogliosis (P<0.001) irrespective of maternal diet. Interesting, offspring born to S-diet-fed mothers and fed the S diet throughout postnatal life became obese despite lower energy intake than controls (P<0.05). These SS offspring showed increased feed efficiency (P<0.001) and reduced fasting pSTAT3 activity (P<0.05) in arcuate nucleus (ARC) compared with other groups. The findings indicated that the combination of the maternal and postnatal S-diet exposure induced persistent changes in leptin signalling, hence affecting energy balance. Thus, appetite regulation was more sensitive to the effect of leptin than energy expenditure, suggesting differential programming of leptin sensitivity in ARC in SS offspring. Effects of the maternal S diet were normalized when offspring were fed a chow diet after weaning. CONCLUSIONS: Maternal intake of chocolate and soft drink had long-term consequences for the metabolic phenotype in the offspring if they continued on the S diet in postnatal life. These offspring displayed obesity despite lowered energy intake associated with alterations in hypothalamic leptin signalling.